A duality result on frame and Riesz sequences - Calderón, Pablo (2019)
In this article we present a short proof of a duality principle concerning frame and Riesz sequences due to Ulanovskii and Olevskii. Our proof is derived from a result on compression on orthogonal projections. As a consequence, we get a better lower frame (Riesz) bound for the sequences than the one deduced from the original proof.